4(3a+3)-(4a+6)=15

Simple and best practice solution for 4(3a+3)-(4a+6)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3a+3)-(4a+6)=15 equation:


Simplifying
4(3a + 3) + -1(4a + 6) = 15

Reorder the terms:
4(3 + 3a) + -1(4a + 6) = 15
(3 * 4 + 3a * 4) + -1(4a + 6) = 15
(12 + 12a) + -1(4a + 6) = 15

Reorder the terms:
12 + 12a + -1(6 + 4a) = 15
12 + 12a + (6 * -1 + 4a * -1) = 15
12 + 12a + (-6 + -4a) = 15

Reorder the terms:
12 + -6 + 12a + -4a = 15

Combine like terms: 12 + -6 = 6
6 + 12a + -4a = 15

Combine like terms: 12a + -4a = 8a
6 + 8a = 15

Solving
6 + 8a = 15

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 8a = 15 + -6

Combine like terms: 6 + -6 = 0
0 + 8a = 15 + -6
8a = 15 + -6

Combine like terms: 15 + -6 = 9
8a = 9

Divide each side by '8'.
a = 1.125

Simplifying
a = 1.125

See similar equations:

| p=13-6 | | 12n+4(n+4)-4(n+1)= | | 12x=15-3x | | 24=-2c | | 48=-4h | | 1-49y^2=0 | | 7(4.4+0.2y)-4y=-7 | | r-6=-10 | | 2/(3(x^(4/3))) | | 100,000*x/9500,000=0.01 | | 10x-2x=x-8 | | 2/(3x^(4/3)) | | 4(2x-3)=1 | | 6=-3+a | | -11=v-7 | | 1+33.1x=4x-10 | | b-9=4 | | 4+b=12 | | 35.28/6.3 | | y=33.1x+1 | | 1x+.2x=246 | | 7/10-3/5= | | 2x-7=11-7 | | 6-2=2+z-2 | | 9(3)-2y=19 | | -5x-7x=x+7 | | y=6sin(4x+7) | | 7x-40=100 | | 20x^2=40x | | -4-5y=21 | | 2(x+1)-5(x+3)=2 | | z^8=-1+i |

Equations solver categories